1997
DOI: 10.1128/jb.179.11.3818-3821.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli flagellar transcriptional activator flhD regulates cell division through induction of the acid response gene cadA

Abstract: FlhD is a positive regulator of cadA. A mutant with a transposon-mediated lacZ fusion to cadA exhibited a cell division phenotype similar to that of the flhD mutant and had FlhD-dependent ␤-galactosidase activity. Under different growth conditions, the cell division rate correlated with the level of expression of cadA.In a previous study (13), we demonstrated that Escherichia coli flhD is involved in a process other than flagellar expression, namely, reducing the cell division rate as cells enter stationary ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…More significantly, the flhDC operon is strongly upregulated during P. mirabilis swarming (29) and contributes to virulence factor expression in several pathogens (4,25,42,80). In addition, microarray comparisons of mRNA levels from E. coli wild-type and flhDC mutant strains have suggested that the flagellar master operon regulates several nonflagellar genes, particularly those involved in cell division (52)(53)(54)(55)(56)67). Thus, the phenotype of the fliL mutation found in this study is likely a consequence of FliL directly or indirectly affecting flhDC expression.…”
Section: Discussionmentioning
confidence: 63%
“…More significantly, the flhDC operon is strongly upregulated during P. mirabilis swarming (29) and contributes to virulence factor expression in several pathogens (4,25,42,80). In addition, microarray comparisons of mRNA levels from E. coli wild-type and flhDC mutant strains have suggested that the flagellar master operon regulates several nonflagellar genes, particularly those involved in cell division (52)(53)(54)(55)(56)67). Thus, the phenotype of the fliL mutation found in this study is likely a consequence of FliL directly or indirectly affecting flhDC expression.…”
Section: Discussionmentioning
confidence: 63%
“…Transcription of these genes, as well as motility, could be restored by addition of signals exogenously, further confirming that regulation of flagellum expression and motility is controlled by a quorum sensing signaling mechanism (74,75). QS regulation of flhDC expression has far-reaching implications beyond flagellum expression, given that FlhDC has been shown to also regulate bacterial cell division (57,58) and several metabolic processes (56). QS regulation of the LEE-encoded TTS system and the flagellum regulon in EHEC is dependent on the AI-3 signal; the role of AI-2 signaling in EHEC remains to be established (75).…”
Section: Quorum Sensing By Gastronintestinal Pathogensmentioning
confidence: 58%
“…The master flagellar operon flhDC also directs transcription of many nonflagellar genes (65). It has been implicated in the regulation of cell division (66,67), and overproduction is known to induce swarming in many enteric bacteria (22). Although the V. parahaemolyticus lateral gene system encodes proton-powered peritrichous flagella that are upregulated in response to growth on a surface, as are the flagella of E. coli and S. enterica, we have discovered that the hierarchy of the laf system is unlike the system of these enteric bacteria.…”
Section: Discussionmentioning
confidence: 91%